2010
DOI: 10.1089/lap.2009.0210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dismembered and Nondismembered Y-V Laparoscopic Pyeloplasty in Patients with Primary Hydronephrosis

Abstract: LY-VP appears to be a safe, attractive alternative to LH-AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…4,6,7,8,15 Three studies report similar therapeutic results. 4,6,7 Klingler and associates 8 reported a considerably lower success rate of Y-V plasty in comparison with A-H plasty, but only five patients constituted the Y-V group and all of them were operated on in the initial stages of the learning curve. Casale and coworkers 16 report the success rate of 94% for A-H plasty and 43% for Heineke-Mikulicz plasty, albeit in children.…”
Section: Szydełko Et Almentioning
confidence: 86%
See 3 more Smart Citations
“…4,6,7,8,15 Three studies report similar therapeutic results. 4,6,7 Klingler and associates 8 reported a considerably lower success rate of Y-V plasty in comparison with A-H plasty, but only five patients constituted the Y-V group and all of them were operated on in the initial stages of the learning curve. Casale and coworkers 16 report the success rate of 94% for A-H plasty and 43% for Heineke-Mikulicz plasty, albeit in children.…”
Section: Szydełko Et Almentioning
confidence: 86%
“…A retrospective data analysis of 90 patients who had undergone laparoscopic pyeloplasty at our institution from 2001 to 2007 indicated that the mean operative time for A-H plasty was considerably longer then for Y-V plasty. 7 Undoubtedly, crossing vessel translocation may affect the operative time. In our study, a crossing vessel was more often observed in the Y-V group than in the A-H group (a statistically significant difference), which might account for the comparable operative times of both procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 In a study comparing laparoscopic Anderson-Hynes pyeloplasty with laparoscopic Y-V pyeloplasty, it was shown that in the Y-V plasty group operative time was significantly shorter and intracorporeal suturing was easier with similar outcomes. 43 In another study that prospectively compared success rates in Anderson-Hynes and Y-V plasty, the former resulted in a higher success rate than Y-V pyeloplasty, but the difference was not statistically significant (Fig. 3).…”
mentioning
confidence: 93%